The categories of infidelity in the Qur'an = Kategori kufur di dalam Qur'an - Abd Rahman, Saodah (International Islamic University Malaysia, 2013)
In the Qur´ān, infidelity is related to the term kufr in general. The word kufr is mentioned in different terms and contexts such as shirk, Ðulm and fisq. Kufr denotes the denial of the Articles of Islamic faith. As regards shirk, it is applied to those who ascribe partners to Allah in word or action, like those who indulge in idolatry. Hence, the Christians who are regarded as the People of the Book are considered to be unbelievers equal to the polytheists due to their belief in the Doctrine of Trinity. The Jews, the other category of the People of the Book, despite their belief in the concept of monotheism (tawÍīd), are also considered to be unbelievers (kāfirūn) in the Qur´ān as a result of changing the laws of God in the Torah. The term Ðulm is directly related to the case of preventing people from worshipping Allah, deviating from the truth of Islam, and preaching against the teachings of the Messengers of Allah and their messages. As for the term Fisq, it is related to the people who, out of their own volition, do not abide by what Allah has revealed. This research tries to explore the contextual interpretation of some passages of the Qur´ān that are related to the term kufr in order to understand various categories of kufr.